Binding Affinity of Potato, Cassava, and Purple Yam Phytochemicals to Fusarium Proteins: Insights from Molecular Docking - Benatar, Gilang Vaza; Hakim, Abdul; Anisah, Siti Nur; Sidiq, Roni Maulan; Tarigan, Rafif Naufal Assadel (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fusarium species are destructive plant pathogens responsible for severe crop losses thereby posing a critical threat to global food security. Sustainable strategies to control Fusarium-induced diseases are urgently needed due to limitations of synthetic fungicides. This study investigated the interaction of phytochemicals from potato (Solanum tuberosum), cassava (Manihot esculenta), and purple yam (Dioscorea alata) with three Fusarium proteins: LaeA, Pep2, and VeA. Protein structures were modeled and validated using stereochemical analyses, followed by molecular docking with representative metabolites, including pyrogallol, cyclogallipharaol, scopoletin, linamarin, cyanidin-3-glucoside, and peonidin-3-glucoside. Docking results showed that potato metabolites exhibited moderate binding activity, cassava metabolites displayed broader inhibitory potential, and purple yam anthocyanins demonstrated the strongest affinities (–6.7 to –7.4 kcal/mol) through multiple hydrogen bonds, hydrophobic contacts, and electrostatic interactions. Among the targets, Pep2 showed consistently stable interactions, while LaeA and VeA exhibited greater flexibility but remained responsive to anthocyanins. These findings highlight the potential of edible crop-derived phytochemicals, particularly anthocyanins and scopoletin, as eco-friendly antifungal agents. The structural basis provided here supports future experimental validation and the development of sustainable crop protection strategies.